PERAN LUMBUNG DESA MODERN DALAM PEMBERDAYAAN EKONOMI RAKYAT - Agung Wibowo (Universitas Sebelas Maret, 2005)
Countryside mow is a house to keep society's paddy. All of society has the same rights to use countryside mow. The basic values of countryside mow is: trust, togetherness, transparency, and democracy. Along the nun of time, the existence of countryside mow is to be lost. The pressure of colonial cause this. Start from, the modern countryside mow is developing now. The countryside mow development is aim to society powered in the case of controling shell of rice price. The modern is the best choice and competent to be government's expectation. The modern countryside mow as saving and loan institute in countryside will be alternative for society to answering the demand offood when dry season. Beside this, the countryside mow is pioneer ofcredit institute, that begining of Badan Kredit Desa (Countryside Credit Institute). Countryside Credit Institut is pioneer of Micro Monetary Institute.